Diagnosis and Management of Cutaneous Psoriasis: A Review. (February 2019) - Brandon, Alisa; Mufti, Asfandyar; Gary Sibbald, R.
Abstract : GENERAL PURPOSE: To provide information about the diagnosis and management of cutaneous psoriasis. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After completing this continuing education activity, the provider should be better able to: Describe the epidemiology, pathophysiology, clinical presentation, assessment, and diagnosis of the types and subtypes of psoriasis. Explain the use of topical treatments, intralesional steroids, phototherapy, conventional systemic treatments, biologic agents, and pain medicines for psoriasis. ABSTRACT: Psoriasis is a chronic inflammatory disease that is characterized by plaque, inverse, guttate, pustular, and erythrodermic variants. This review focuses on the epidemiology, diagnosis, and treatment of cutaneous psoriasis. Other related topics discussed include peristomal psoriasis, the Koebner phenomenon, and the relationship between biologic therapy and wound complications.